2000
DOI: 10.1007/s12043-000-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sprayed alumina coatings for radiation detector development

Abstract: Conventional design of radiation detectors uses sintered ceramic insulating modules. The major drawback of these ceramic components is their inherent brittleness. Ion chambers, in which these ceramic spacers are replaced by metallic components with plasma spray coated alumina, have been developed in our Research Centre. These components act as thin spacers that have good mechanical strength as well as high electrical insulation and replace alumina insulators with the same dimensions. As a result, the design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…McPherson [12,13] reported that during solidification of molten droplets at higher cooling rates, the formation of γ-Al 2 O 3 is more favoured than α-Al 2 O 3 as the free energy barrier to nucleation was low for the formation of γ-Al 2 O 3 . Alex et al [1] evaluated the coating characteristics of plasma-sprayed alumina coatings on copper, aluminium and stainless steel components for neutron and gamma detector applications. However, the adhesion strength and thermal cycling studies were not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…McPherson [12,13] reported that during solidification of molten droplets at higher cooling rates, the formation of γ-Al 2 O 3 is more favoured than α-Al 2 O 3 as the free energy barrier to nucleation was low for the formation of γ-Al 2 O 3 . Alex et al [1] evaluated the coating characteristics of plasma-sprayed alumina coatings on copper, aluminium and stainless steel components for neutron and gamma detector applications. However, the adhesion strength and thermal cycling studies were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…The monolithic ceramic insulating discs/spacers used in nuclear reactors are prone to failure during seismic vibration and shock. Therefore, the feasibility of using metallic parts coated with high-purity alumina by plasma spraying was explored and was found to be useful [1]. There is a need for using such ceramic insulated neutron detectors in the prototype fast breeder reactor, under construction in Kalpakkam.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a higher thickness of coating (increased volume fraction) may affect the neutronic balance and thermal diffusivity while lesser thickness impacts the oxidation shielding. Lesser electrical insulation resistance was also linked to lesser thickness of plasma sprayed Al 2 O 3 coating 49 . A typical picture of both types of specimens i.e.…”
Section: Materials Characterization and Methodologymentioning
confidence: 95%
“…Carbon nanotubes (CNTs) have attracted much attention as a potential reinforcement for the enhancement of toughness [1][2][3][4][5][6] and wear resistance [7][8][9][10] of the ceramic matrix due to their remarkable mechanical [11][12][13][14][15] and thermal properties [16,17]. In the past, researchers have addressed the tribological behavior of CNT reinforced aluminum oxide (Al 2 O 3 ) composite [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%